Characterization and anaerobic treatment of the sanitary landfill leachate in Istanbul - (:unkn) unknown (I W A PUBLISHING, 2000)
In this study, characterization and anaerobic treatability of leachate from Komurcuoda Sanitary Landfill located on the Asian part of Istanbul were investigated. Time based fluctuations in characteristics of leachate were monitored for an 8 month period. Samples were taken from a 200 m(3) holding tank located at the lowest elevation of the landfill. COD concentrations have ranged between 18800 and 47800 mg/l while BOD5 between 6820 and 38500 mg/L. COD and BOD5 values were higher in summer and lower in winter due to dilution by precipitation. On the other hand, it was quite interesting that such a dilution effect was not observed for ammonia. The highest ammonia concentration, 2690 mg/L was in November 1998. BOD5/COD ratio was larger than 0.7 for most samples indicating high biodegradability, and acidic phase of decomposition in the landfill. For anaerobic treatability, three different reactors, namely an upflow anaerobic sludge bed reactor, an anaerobic upflow filter and a hybrid bed reactor, were used. The anaerobic reactors were operated for more than 230 days and were continuing operation when this paper was prepared. Organic loading was increased gradually from 1.3 kgCOD/m(3).day to 8.2 kg COD/m(3).day while hydraulic retention time was reduced from 2.4 days to 2.0 days. All the reactors showed similar performances against organic loadings with efficiencies between 80% and 90%. However the reactors have experienced high ammonia concentrations several times throughout the experimental period, and showed different inhibition levels. Anaerobic filter was the least affected reactor while UASB was the most. Hybrid bed reactor has exhibited a similar performance to anaerobic filter although not to the same degree.
Keywords: solid wastes; leachate; sanitary landfills; anaerobic treatment; inhibition